Molecular basis of the structural stability of hemochromatosis factor E: A combined molecular dynamic simulation and GdmCl‐induced denaturation study. Issue 3 (March 2016) - Khan, Parvez; Parkash, Amresh; Islam, Asimul; Ahmad, Faizan; Hassan, Md. Imtaiyaz
ABSTRACT: Hemochromatosis factor E (HFE) is a member of class I MHC family and plays a significant role in the iron homeostasis. Denaturation of HFE induced by guanidinium chloride (GdmCl) was measured by monitoring changes in [ θ ]222 (mean residue ellipticity at 222 nm), intrinsic fluorescence emission intensity at 346 nm (F346 ) and the difference absorption coefficient at 287 nm (Δ ε 287 ) at pH 8.0 and 25°C. Coincidence of denaturation curves of these optical properties suggests that GdmCl‐induced denaturation (native (N) state ↔ denatured (D) state) is a two‐state process. The GdmCl‐induced denaturation was found reversible in the entire concentration range of the denaturant. All denaturation curves were analyzed for Δ G D 0, Gibbs free energy change associated with the denaturation equilibrium (N state ↔ D state) in the absence of GdmCl, which is a measure of HFE stability. We further performed molecular dynamics simulation for 40 ns to see the effect of GdmCl on the structural stability of HFE. A well defined correlation was established between in vitro and in silico studies. © 2015 Wiley Periodicals, Inc. Biopolymers 105: 133–142, 2016.